Correlations between well-being of nurses and psychosocial working conditions – a descriptive cross-sectional study - Tomaszewska, Katarzyna; Kowalczuk, Krystyna; Majchrowicz, Bożena (Frontiers in Public Health, 2024)
Introduction: Work in health care is classified as a difficult profession and nurses are considered among the professional group that is exposed to the permanent impact of occupational stress. Psychosocial working conditions and related hazards are defined as those aspects that have the potential to cause harm to an employee's mental or physical health. Lack of psycho-physical health well-being reduces job satisfaction and thus job commitment. Aim: The aim of this study was to assess the overall well-being of nurses and examine the correlation between nurses' well-being and their assessment of psychosocial working conditions in conjunction with occupational and demographic factors. Material and methods: A descriptive cross-sectional survey was conducted among 526 nurses employed in a selected public clinical hospital in Poland. All nurses provided labor during the survey. A diagnostic survey method using the standardized Psychosocial Working Conditions questionnaire based on the demands-control-support stress model was used for measurement. Results: The examined nurses rated highly job demands (mean 3.46) as well as the scale of desired changes (mean 3.44). The ability to control their work (mean 3.19) and the level of social support (mean 3.21) were rated at a slightly lower level. The scale of well-being was rated highest by respondents (mean 3.68). Several statistically significant correlations (p<0.05) can be observed between the well-being scale and the other scales of psychosocial working conditions across age categories. The least correlated are the well-being and demands scales, although as age increases with higher levels of well-being, the demands scale scores decrease. Conclusions: The well-being of the examined nurses was closely related to sociodemographic data and the individual scales of the Psychosocial Working Conditions questionnaire. Chronic diseases are associated with greater demands at work and reduced well-being. Respondents who receive higher levels of support at work experience higher levels of well-being.